Effects of Hormonal Contraception Use on Cognitive Functions in Patients With Bulimia Nervosa - Nobile, Benedicte; Maimoun, Laurent; Jaussent, Isabelle Danielle; Seneque, Maude; Dupuis-Maurin, Kathlyne; Lefebvre, Patrick; Courtet, Phillippe; Renard, Eric; Guillaume, Sebastien (Frontiers in Psychiatry, 2021)
Background: Growing evidences indicate that sex hormones have an effect on cognitive functions, and that Bulimia Nervosa (BN) is associated with cognitive impairment. The aim of this study was to determine the effect of hormonal contraception (HC) use on four cognitive functions that are impaired in patients with BN. Methods: This retrospective exploratory study included 103 women with a diagnosis of BN based on the DSM-5 criteria. Their age ranged from 15 to 45 years, and 46.6% were taking HC (oral, transdermal, or intrauterine). Cognition was assessed with the d2 test (attention), Iowa gambling task (IGT; decision making), Brixton spatial anticipation test (set shifting), and Rey-Osterrieth complex figure test (central coherence). Data were analyzed with logistic regression models to estimate the adjusted odds ratios (OR) and 95% confidence intervals (CI) of HC effect on the neuropsychological test scores. Results: In the multivariate model, HC use was significantly associated with better scores for two d2 test indexes: F-score (OR=0.98, 95% CI=[0.95; 0.99]) and final total score ratio (OR=0.87, 95% CI=[0.77; 0.99]). HC was also associated with better understanding of the IGT explicit rules. No difference between groups (HC and non-HC use) was detected for set shifting and central coherence. Conclusions: This exploratory study suggests that HC could have effects on sustained attention and concentration in women with BN. More studies are needed to confirm these results.